SUSTAINABILITY ANALYSIS OF MANGROVE ECOSYSTEMSIN SUNGAI BELA VILLAGE, INDRAGIRI HILIR REGENCY - Mohd Riza Fahlifi; Deni Efizon; Adriman Adriman (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This study aims to determine the level of sustainability of mangrove ecosystems in Sungai Bela Village. The method used in this study is a survey method with data analysis using the Multi Dimensional Scaling (MDS). The results showed that the index value of the sustainability of mangrove ecosystems showed an ecological dimension(61.42) with RMS (2.28), social, economic and cultural dimensions (50.91) with RMS (2.51), legal and institutional dimensions (61.91) with RMS (1.79).Several factors that affect the sustainability of mangrove ecosystems such as:(1) mangrove species diversity;(2) density of mangrove ecosystems;(3) content of sediment organic matter;(4) marketing of fishery products;(5) mangrove dependence on livelihoods;(6) level of community knowledge;(7) the role of community leaders;(8) level of community compliance and (9) community participation.It can be concluded that the mangrove ecosystem in Sungai Bela Village with a sufficiently continuous status.